The role of heat stress on the age related protein carbonylation - SÖZEN, AHMET ERDİ; YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE BV, 2013)
Since the proteins are involved in many physiological processes in the organisms, modifications of proteins have important outcomes. Protein modifications are classified in several ways and oxidative stress related ones take a wide place. Aging is characterized by the accumulation of oxidized proteins and decreased degradation of these proteins. On the other hand protein turnover is an important regulatory mechanism for the control of protein homeostasis. Heat shock proteins are a highly conserved family of proteins in the various cells and organisms whose expressions are highly inducible during stress conditions. These proteins participate in protein assembly, trafficking, degradation and therefore play important role in protein turnover. Although the entire functions of each heat shock protein are still not completely investigated, these proteins have been implicated in the processes of protection and repair of stress-induced protein damage. This study has focused on the heat stress related carbonylated proteins, as a marker of oxidative protein modification, in young and senescent fibroblasts. The results are discussed with reference to potential involvement of induced heat shock proteins. This article is part of a Special Issue entitled: Protein Modifications. Biological significance Age-related protein modifications, especially protein carbonylation take a wide place in the literature. In this direction, to highlight the role of heat shock proteins in the oxidative modifications may bring a new aspect to the literature. On the other hand, identified carbonylated proteins in this study confirm the importance of folding process in the mitochondria which will be further analyzed in detail. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aging; Carbonylation; Heat shock protein; Degradation; CHAPERONE-MEDIATED AUTOPHAGY; SENESCENT HUMAN-FIBROBLASTS; DISULFIDE BOND FORMATION; BLOOD MONONUCLEAR-CELLS; SHOCK GENE-EXPRESSION; OXIDATIVE STRESS; ENDOPLASMIC-RETICULUM; 26S PROTEASOME; GLUTATHIONE-REDUCTASE; ATP SYNTHASE